Determinants of maximal cycling power: crank length, pedaling rate and pedal speed - Martin, J. C.; Spirduso, W. W. (European Journal of Applied Physiology, 2001)
The purpose of this investigation was to determine the effects of cycle crank length on maximum cycling power, optimal pedaling rate, and optimal pedal speed, and to determine the optimal crank length to leg length ratio for maximal power production. Trained cyclists (n=16) performed maximal inertial load cycle ergometry using crank lengths of 120, 145, 170, 195, and 220 mm. Maximum power ranged from a low of 1149 (20) W for the 220-mm cranks to a high of 1194 (21) W for the 145-mm cranks. Power produced with the 145- and 170-mm cranks was significantly (P<0.05) greater than that produced with the 120- and 220-mm cranks. The optimal pedaling rate decreased significantly with increasing crank length, from 136 rpm for the 120-mm cranks to 110 rpm for the 220-mm cranks. Conversely, optimal pedal speed increased significantly with increasing crank length, from 1.71 m/s for the 120-mm cranks to 2.53 m/s for the 220-mm cranks. The crank length to leg length and crank length to tibia length ratios accounted for 20.5% and 21.1% of the variability in maximum power, respectively. The optimal crank length was 20% of leg length or 41% of tibia length. These data suggest that pedal speed (which constrains muscle shortening velocity) and pedaling rate (which affects muscle excitation state) exert distinct effects that influence muscular power during cycling. Even though maximum cycling power was significantly affected by crank length, use of the standard 170-mm length cranks should not substantially compromise maximum power in most adults.